His-Purkinje system pacing reduced tricuspid regurgitation in patients with persistent atrial fibrillation after left-sided valve surgery - Wang, Ning; Zhu, Tianyu; Li, Yan; Cheng, Guanliang; Chen, Yu; Fu, Yuwei; Chen, Xuezhi; Liu, Xiaohui (Frontiers in Cardiovascular Medicine, 2023)
Background & objective Tricuspid regurgitation after left-sided valve surgery was a common and difficult problem. Atrial fibrillation was considered to be an important etiology of tricuspid regurgitation. His-Purkinje system pacing (HPSP) was a physiological pacing method, which could prevent and treat heart failure and might reduce tricuspid regurgitation. Our study aimed to investigate the effect of HPSP on tricuspid regurgitation in patients with persistent atrial fibrillation after left-sided valve surgery. Methods This study was a retrospective study. The 3-year patient review focused on those who underwent permanent cardiac pacemaker implantation of HPSP after mitral valve and/or aortic valve replacement from Jan 1st, 2019 to Jan 1st, 2022. HPSP included His bundle pacing (HBP) or left bundle branch pacing (LBBP). Clinical data collected included electrocardiogram, pacing parameters, ultrasonic cardiogram parameters and chest x-ray at implantation and 3-month follow up. Univariate and multivariate linear regression analysis of tricuspid regurgitation velocity were performed. Results A total of 44 patients was retrospectively reviewed. Eight patients who had undergone implantation of HPSP after left-sided heart valve replacement were enrolled in the study. All patients had persistent atrial fibrillation. Three of them received HBP and five underwent LBBP. At 3-month follow-up, the tricuspid regurgitation grade was significantly lower than that before implantation (P = 0.007). The tricuspid regurgitation velocity significantly decreased (317 ± 74 cm/s vs. 261 ± 52 cm/s, P = 0.022) and tricuspid valve pressure gradient (PG) reduced (42 ± 21 mmHg vs. 28 ± 10 mmHg, P = 0.040). The cardiothoracic ratio of patients was significantly lower than that before implantation (0.61 ± 0.08 vs. 0.64 ± 0.09, P = 0.017). The NYHA classification of patients also improved (P = 0.013). In multivariate liner regression analysis, the pacing ratio (β = 0.736, P = 0.037) was an independent determinant of tricuspid regurgitation velocity variation. Conclusion HPSP might reduce tricuspid regurgitation and improve cardiac function in patients with persistent atrial fibrillation after left-sided valve surgery.